Anisotropy of magnetic susceptibility of Eocene and Miocene sediments in the Qaidam Basin, Northwest China: Implication for Cenozoic tectonic transition and depocenter migration - Xiangjiang Yu; Baochun Huang; Shuwei Guan; Suotang Fu; Feng Cheng; Xiang Cheng; Tuo Zhang; Zhaojie Guo (Geochemistry, Geophysics, Geosystems, 2014)
Abstract The Cenozoic evolution of the Qaidam basin, especially its paleostress field, can provide a better understanding of the dynamistic process of the northern Tibetan Plateau. Under certain conditions, Anisotropy of Magnetic Susceptibility (AMS) holds great potential for investigating early tectonic events, even where macroscopic and microscopic evidence of deformation is invisible. A basin‐scale AMS study of the middle to late Eocene Xiaganchaigou Formation and the early to middle Miocene Xiayoushashan Formation from seven locations was conducted, covering most outcrops of these two formations within the Qaidam basin. In the western Qaidam basin, principal stress directions inferred from AMS ellipsoids consist with those inferred from fold axial traces, while at Eboliang and in the northern Qaidam basin, most principal stress directions reflected by AMS ellipsoids are different from those reflected by fold axial traces. Two epochs of compressive strain have been identified: an early N‐S strain no later than Oligocene and a late NE‐SW strain since Miocene. The early N‐S compression is more intense in the northern Qaidam basin than that in the western Qaidam basin, while the late NE‐SW compression, which dominates the modern NW‐SE trending fold axial traces, is more intense in the western Qaidam basin than that in the northern Qaidam basin. The stress transfer provides a reasonable explanation for the southeastward migration of the deposition center in the Qaidam basin during Cenozoic. Moreover, the appearance of E‐component compression may be in close relationship with the beginning of the left‐lateral strike‐slip Kunlun Fault or the eastward channel flow to the south of the Kunlun Fault.